Clinical prognosis of FLAIR hyperintense arteries in ischaemic stroke patients: a systematic review and meta-analysis. Issue 5 (26th March 2020) - Zhou, Zien; Malavera, Alejandra; Yoshimura, Sohei; Delcourt, Candice; Mair, Grant; Al-Shahi Salman, Rustam; Demchuk, Andrew M; Wardlaw, Joanna M; Lindley, Richard I; Anderson, Craig S
Abstract : Objective: We performed a systematic review and meta-analysis to determine the association of fluid-attenuated inversion recovery (FLAIR) hyperintense arteries (FLAIR-HAs) on brain MRI and prognosis after acute ischaemic stroke (AIS). Methods: We searched Medline, Embase and Cochrane Central Register of Controlled Trials for studies reporting clinical or imaging outcomes with presence of FLAIR-HAs after AIS. Two researchers independently assessed eligibility of retrieved studies and extracted data, including from the Enhanced Control of Hypertension and Thrombolysis Stroke Study (ENCHANTED). Outcomes were unfavourable functional outcome (primary, modified Rankin scale scores 3–6 or 2–6), death, intermediate clinical and imaging outcomes. We performed subgroup analyses by treatment or types of FLAIR-HAs defined by location (at proximal/distal middle cerebral artery (MCA), within/beyond diffusion-weighted imaging (DWI) lesion) or extent. Results: We included 36 cohort studies (33 prospectively collected) involving 3577 patients. FLAIR-HAs were not associated with functional outcome overall (pooled risk ratio 0.87, 95% CI 0.71 to 1.06), but were significantly associated with better outcome in those receiving endovascular therapy (0.56, 95% CI 0.41 to 0.75). Contrary to FLAIR-HAs at proximal MCA or within DWI lesions, FLAIR-HAs beyond DWI lesions were associated with better outcome (0.67, 95% CI 0.57 to 0.79). FLAIR-HAs favoured recanalisation (1.21, 95% CI 1.06 to 1.38) with increased risk of intracerebral haemorrhage (2.07, 95% CI 1.37 to 3.13) and early neurological deterioration (1.93, 95% CI 1.30 to 2.85). Conclusions: FLAIR-HAs were not associated with functional outcome overall but were associated with outcome after endovascular therapy for AIS. FLAIR-HAs were also associated with early recanalisation or haemorrhagic complications, and early neurologic deterioration. PROSPERO registration number: CRD42019131168.